2016
DOI: 10.14257/astl.2016.131.12
|View full text |Cite
|
Sign up to set email alerts
|

Social structural Determinants of Regional Variations in Fertility

Abstract: In this paper, a path analysis was carried out to identify socialstructural determinants of regional fertility. As a result, urbanization appeared to affect on marriage behavior and fertility through altering age structure, distribution of educational attainment and jobs among the population at the regional level. Thus, the population, size and structure, appeared to be determined not only by the natural factor, fertility birth rate, but also by socialstructural factors (education, job) of the region. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The result confirms that the relationship between local-level TFRs and the selected sociodemographic factors varies across regions in both magnitude and direction. Although various studies of fertility in South Korea have explored geographical variations in fertility based on rural and urban settings [14,15], this study shows that responses of local-level total fertility rates to sociodemographic factors spatially vary beyond the crude rural and urban dichotomy.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The result confirms that the relationship between local-level TFRs and the selected sociodemographic factors varies across regions in both magnitude and direction. Although various studies of fertility in South Korea have explored geographical variations in fertility based on rural and urban settings [14,15], this study shows that responses of local-level total fertility rates to sociodemographic factors spatially vary beyond the crude rural and urban dichotomy.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, the aim of this study is to In spite of various fertility theories to support fertility variations due to different geographical settings [11], studies examining spatial heterogeneity of fertility in South Korea are scarce. Previous research has shown the regional differences of fertility in South Korea on the basis of the underlying assumption of demographic transition theory [2,12,13], reaching the overriding conclusion that fertility levels were significantly lower in urban areas than rural areas [10,14,15]. While urban-rural analysis shed considerable light on geographical variations in fertility behavior in South Korea, the traditional urban-rural dichotomy is criticized as geographically crude [16].…”
Section: Introductionmentioning
confidence: 99%